PROBLEMS OF MODERN PHILOLOGY: CHALLENGES OF TIME AND PATHS OF DEVELOPMENT - Baxtiyorova Nozima Otabek qizi (TALABALAR ILMIY KONFERENSIYASI "TILSHUNOSLIK MASALALARI – YOSH TADQIQOTCHILAR NIGOHIDA", 2025)
The article examines the main problems faced by modern philology in the context of globalization, digitalization and transformation of humanitarian knowledge. The article analyzes such issues as the decline in interest in philological disciplines, the fragmentation of science, the impact of digital technologies, the revision of the literary canon, ethical challenges and the personnel crisis. Special attention is paid to the need for an interdisciplinary approach, adaptation to modern media, and preservation of linguistic and cultural heritage. It is concluded that philology is at the stage of rethinking its goals and must actively interact with society in order to preserve its scientific and cultural significance.